Обнаружение личинок слепней, зараженных энтомопатогенным грибом — Coelomomyces milkoi (Phycomycetes, Coelomomycetaceae) на берегах рек бассейна Северского Донца - Шевцова, Н.П.; Андреева, Р.В. (Вестник зоологии, 1975)
On the banks of three rivers in the Seversky Donets basin (the Voroshilovgrad and Kharkov Regions) Tabanus autumnalis L. larvae infected with entomopathogenic fungus Coelomomyces milkoi are found. A brief description of the larvae habitats and data on their infestation extensiveness in 1971-1973 are presented.